Exchange Rate Forecasting Techniques, Survey Data, and Implications for the Foreign Exchange Market. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This paper examines the dynamics of the foreign exchange market. The first half addresses a number of key questions regarding the forecasts of future exchange rates made by market participants, by means of updated estimates using survey data. Here we follow most of the theoretical and empirical literature in acting as if all market participants share the same expectation. The second half then addresses the possibility of heterogeneous expectations, particularly the distinction between 'chartists' and 'fundamentalists,' and the implications for trading in the foreign exchange market and for the formation of speculative bubbles.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet